Fusarium graminearum infection during the reproductive stages of closed-flowering barley, grain deoxynivalenol contamination, and response to fungicide application - Gabriel, Lorrant Cavanha; Rodrigues, Paula Cristina dos Santos; Angelotti-Zampar, Priscila; Feksa, Heraldo Rosa; Tessmann, Dauri José (Pesquisa Agropecuaria Brasileira, 2024)
The objective of this work was to investigate the influence of the reproductive stage of closed-flowering barley on Fusarium graminearum infection and to evaluate the efficacy of pre-inoculation fungicide application in controlling Fusarium head blight (FHB) and reducing grain contamination with the deoxynivalenol (DON) mycotoxin. Two experiments, in a completely randomized design with eight replicates, were conducted in a growth chamber at different temperatures. The statistical analysis was nonparametric, using the Kruskal-Wallis test. Potted plants of the BRS BRAU barley cultivar were inoculated by spraying a conidial suspension at the following three reproductive stages: anthesis halfway, grain at medium milk, and soft dough. The tebuconazole fungicide was sprayed 48 hours before pathogen inoculation. The FHB symptoms caused by the inoculation with F. graminearum at the medium milk stage are fully visible, although fungicide application before pathogen inoculation controls the disease, but mild at the anthesis halfway and soft dough stages. Inoculation at the three stages results in grain contamination with DON, which is reduced by pre-inoculation fungicide application.